(untitled) (Journal of actual problems of jurisprudence, 2016)
Judicial control to some extent is present at all forms of realization of the state legal policy. However, the control exercised by court during pre-judicial production is most specific. It is carried out not only in traditionally inherent administrative justice in the form of consideration of complaints of participants of criminal legal proceedings (as a rule, the parties of protection) on decisions and the actions (inaction) of bodies of criminal prosecution violating and otherwise the limiting rights and freedoms of these participants, but also in the form of giving permission of the separate acts of preliminary investigation (resolution) limiting constitutional rights and freedoms of citizens. This article is devoted to a ratio of judicial control and public prosecutor’s supervision in criminal legal proceedings of the Republic of Kazakhstan. In article the general characteristic and concept judicial конторля, its signs, and also distinction from public prosecutor’s supervision are considered. Different views of scientists are analyzed. The author states also the point sight on this problem.